Project Risks and Risky Projects - Michelberger, Pál; Kemendi, Ágnes (International Journal of Engineering and Management Sciences, 2021)
Projects are key drivers of organizational change, both their failure and success can have significant impact on the organizational performance. Risks may arise throughout the entire project life cycle. Managing these and initial project planning uncertainties is an important task of Project Management. The study describes the application of traditional project management tools and methods in risk analysis, -evaluation and -treatment based on modern project and risk management standards and recommendations. The authors also examine the link between classic project management objectives (project time - resources – scopes) and risk-based decision-making. The different scale and scope of projects call for different responses to the associated risks. The study highlights the possible role of the ISO 31000 risk management standard package in project risk management. The authors analyse the risk management of the different projects on the basis of processing relevant literature, including the relationship of the project stakeholders to the risks. R&D, agile projects and project portfolios have specific and complex risk exposures, but their project management can provide several „hidden” risk analysis and - treatment functions.